Effects of polysaccharide-based coating conjugated with silver nanoparticles on shelf-life extension of papaya (Carica papaya L. cv. Eksotika) - Mustaffa @ Hamzah, Hanisah (2014)
Papaya is a tropical fruit that is well accepted worldwide for its good taste and nutritional content. However, like many other tropical fruits, papaya also has postharvest problems due to several reasons including short shelf life caused by disease mainly fungal infection. This problem also affects Carica papaya L. cv. Eksotika, which is one of the popular papaya cultivars in Malaysia. In the present study, polysaccharide-based coatings incorporated with silver nanoparticles were used to prolong the shelf life of Eksotika papaya. In this study, a two-factor central composite design (CCD) was used to optimize two different edible coating formulations for coating of Eksotika papaya. The effect of two different coating formulations, namely, chitosan-based [chitosan (0.5 – 2.5%) and glycerol (0 – 2%)] and carrageenan-based [carrageenan (0.2 – 0.8%) and glycerol (0 – 1%)] on texture and colour components (L, a and b values) of coated papaya were evaluated. From the multiple response optimization analysis, combination of 2.32% chitosan with 0.53% glycerol, and 0.78% carrageenan with 0.85% glycerol for chitosan-based and carrageenan-based coating respectively were predicted to give desirable effect to the response variables tested, with no significant (p > 0.05) difference between the experimental and predicted values. However, during shelf life monitoring of the coated samples, papaya coated with the optimized chitosan-based formulation failed to ripen. In order to overcome this, visual observation of papaya coated with different concentrations of chitosan (0.5, 1.0, 1.5 and 2.32%) were conducted. 1% chitosan was found to successfully coat papaya without retarding the ripening process. Silver nanoparticles at the range of 0-80 ppm were incorporated into the chitosanand carrageenan-based coatings to evaluate the antimicrobial properties of the formed polysaccharide-silver nanocomposites. Chitosan alone without synergistic interaction with silver nanoparticles was sufficient in giving bactericidal and antifungal effects. Carrageenan on the other hand requires addition of 2.5 and 30 ppm of silver nanoparticles to give antifungal and bactericidal effects respectively. Application of chitosan, carrageenan-silver nanocomposite and carrageenan-based coating on Eksotika papaya were able to prolong the shelf life up to 13, 11 and 9 days at ambient condition (26±2°C;70±10% RH), respectively. During low temperature (15±1°C; 60±10% RH) storage, the shelf life was extended up to 21 days for chitosan and carrageenan-silver nanocomposite based coating and also 17 days for carrageenan-based coating. The maximum shelf life of uncoated papaya was 7 and 13 days at ambient and low temperature, respectively. Shelf life extension of coated papaya was judged based on no visible fungal decay. Physiological and physico-chemical evaluations during storage showed that there was no significant (p > 0.05) difference between coated samples and control except for firmness at ambient condition and also total soluble solids. The microbial counts between coated and uncoated papaya were also found to be insignificant (p > 0.05). Determination of silver concentration in papaya fruit coated with carrageenan-silver nanocomposite revealed that, silver migrated through the peel and into the innermost pulp layer of papaya during storage. Consumer acceptance test showed that scores of all tested attributes for coated samples were above the minimum acceptable value (>5). This indicated that the coating did not give negative visual or physical perception towards the consumer. Hence, coating gave positive contribution on shelf life extension of papaya especially for marketing purposes, but incorporation of silver nanoparticles needs to be reconsidered since silver migrated into the pulp due to the thin peel layer of papaya fruit.